Relating to Tradition : Civil Religion and the Evangelical Lutheran Church on Finnish Independence Day - Kyyrö Jere (Finnish Society for the Study of Religion, 2025)
By analysing a survey and elicited thematic writings, this article seeks to identify the main elements in the civil religion (CR) of Finnish Independence Day (FID) celebrations, how FID is related to CR, and the role the Evangelical Lutheran Church of Finland (ELCF) plays in FID. It further demonstrates the utility of an open definition of CR in which its relationship with church religion is understood as an open question and tests the various dimensions of CR presented in previous discussions. The CR of FID celebrations centres on its traditional mode in the memory of war and employs other national symbols. The negotiating mode is favoured by younger generations and distances itself from the rituals of the traditional mode, while the critical mode uses the rejection of FID celebrations as a platform for a general social critique. Membership of the ELCF, Finnish as a mother tongue, higher education levels, and an identification with higher social classes are the most important predictors for celebrating FID. In the writings the ELCF’s role is associated with the traditional mode in blending with the backdrop of other national symbols, especially those related to the war.